FLIPPED INSTRUCTION FOR SPEAKING CLASS: A CLASSROOM ACTION RESEARCH FOR ENHANCING STUDENTS’ ENGAGEMENT - Titik Rahayu; Imam Mudofir; Alief Sutantohadi (Humaniora Scientia, 2019)
Flipped instruction becomes an innovative strategy to be used in the development of technology in which students can access the learning materials online. Before class activities, students are given with adequate materials, thus when they are in class they can focus to do practices related to the topic. Several studies have investigated the use of flipped instruction in the teaching learning process and it can be the response for the today’s needs of students who have difficulties in engaging classroom activities due to the lack of preparation or understanding towards the given materials. In this research, researchers used flipped instruction to increase the engagement of second-semester students in Intermediate Speaking Class, State Polytechnic of Madiun in the academic year of 2018/2019. The researchers conducted classroom action research for 22 students in two cycles. The findings showed that the students engaged in the teaching-learning activities very well and they were well-prepared to speak in front of the class. Moreover, the scores of speaking performance showed improvement. Keywords: flipped instruction, speaking, students’ engagement